Viral suppression and HIV-1 drug resistance 1 year after pragmatic transitioning to dolutegravir first-line therapy in Malawi: a prospective cohort study. Issue 8 (August 2022) - Schramm, Birgit; Temfack, Elvis; Descamps, Diane; Nicholas, Sarala; Peytavin, Gilles; Bitilinyu-Bangoh, Joseph E; Storto, Alexandre; Lê, Minh P; Abdi, Basma; Ousley, Janet; Kalua, Thokozani; Calvez, Vincent; et al.
Summary: Background: Many countries are now replacing non-nucleoside reverse transcriptase inhibitor (NNRTI)-based first-line antiretroviral therapy (ART) with a regimen containing tenofovir disoproxil fumarate, lamivudine, and dolutegravir (TLD). Recognising laboratory limitations, Malawi opted to transition those on NNRTI-based first-line ART to TLD without viral load testing. We aimed to assess viral load and HIV drug resistance during 1 year following transition to TLD without previous viral load testing. Methods: In this prospective cohort study, we monitored 1892 adults transitioning from NNRTI-based first-line ART to the TLD regimen in the Médecins Sans Frontières-supported decentralised HIV programme in Chiradzulu District, Malawi. Eligible adults were enrolled between Jan 17 and May 11, 2019, at Ndunde and Milepa health centres, and between March 8 and May 11, 2019, at the Boma clinic. Viral load at the start of the TLD regimen was assessed retrospectively and measured at month 3, 6, and 12, and additionally at month 18 for those ever viraemic (viral load ≥50 copies per mL). Dolutegravir minimal plasma concentrations (Cmin ) were determined for individuals with viraemia. Drug-resistance testing was done at the start of TLD regimen and at viral failure (viral load ≥50 copies per mL, followed by viral load ≥500 copies per mL; resistance defined as Stanford score ≥15). Findings: Of 1892 participants who transitioned to the TLD regimen, 101 (5·3%) were viraemic at TLD start. 89 of 101 had drug-resistance testing with 31 participants (34·8%) with Lys65Arg mutation, 48 (53·9%) with Met184Val/Ile, and 42 (40·4%) with lamivudine and tenofovir disoproxil fumerate dual resistance. At month 12 (in the per-protocol population), 1725 (97·9% [95% CI 97·1–98·5]) of 1762 had viral loads of less than 50 copies per mL, including 83 (88·3% [80·0–94·0]) of 94 of those who were viraemic at baseline. At month 18, 35 (97·2% [85·5–99·9]) of 36 who were viraemic at TLD start with lamivudine and tenofovir disoproxil fumarate resistance and 27 (81·8% [64·5–93·0]) of 33 of those viraemic at baseline without resistance had viral load suppression. 14 of 1838 with at least two viral load tests upon transitioning had viral failure (all with at least one dolutegravir Cmin value <640 ng/mL; active threshold), suggesting suboptimal adherence. High baseline viral load was associated with viral failure (adjusted odds ratio [aOR] 14·1 [2·3–87·4] for 1000 to <10 000 copies per mL; aOR 64·4 [19·3–215·4] for ≥10 000 copies per mL). Two people with viral failure had dolutegravir resistance at 6 months (Arg263Lys or Gly118Arg mutation), both were viraemic with lamivudine and tenofovir disoproxil fumarate resistance at baseline. Interpretation: High viral load suppression 1 year after introduction of the TLD regimen supports the unconditional transition strategy in Malawi. However, high pre-transition viral load, ongoing adherence challenges, and possibly existing nucleoside reverse transcriptase inhibitor resistance can lead to rapid development of dolutegravir resistance in a few individuals. This finding highlights the importance of viral load monitoring and dolutegravir-resistance surveillance after mass transitioning to the TLD regimen. Funding: Médecins Sans Frontières. Translations: For the French and Portuguese translations of the abstract see Supplementary Materials section.